2017
DOI: 10.1016/j.apradiso.2017.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fuel using the Direct LSC method determination of bio-originated fuel in the presence of quenching

Abstract: A modified version of the Direct LSC method to correct for quenching effect was investigated for the determination of bio-originated fuel content in fuel samples produced from multiple biological starting materials. The modified method was found to be accurate in determining the percent bio-originated fuel to within 5% of the actual value for samples with quenching effects ≤43%. Analysis of highly quenched samples was possible when diluted with the exception of one sample with a 100% quenching effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The direct measurement of the 14 C activity of liquid fuels by liquid scintillation counter (LSC) is a fast method but burdened by some disadvantages. For example, the color of fuels causes different quenching properties in the scintillation cocktail and affects the measurement efficiency (Doll et al 2017). Based on the measurement of radiocarbon content as 14 C/ 12 C and 14 C/ 13 C isotope ratio, the biogenic fraction is also measurable by accelerator mass spectrometry (AMS), where the number of 12 C, 13 C, and 14 C atoms can be counted directly (Bronić et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The direct measurement of the 14 C activity of liquid fuels by liquid scintillation counter (LSC) is a fast method but burdened by some disadvantages. For example, the color of fuels causes different quenching properties in the scintillation cocktail and affects the measurement efficiency (Doll et al 2017). Based on the measurement of radiocarbon content as 14 C/ 12 C and 14 C/ 13 C isotope ratio, the biogenic fraction is also measurable by accelerator mass spectrometry (AMS), where the number of 12 C, 13 C, and 14 C atoms can be counted directly (Bronić et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Details of method preparation will not be described in detail here, but it is noted that more in-depth preparation, such as benzene synthesis, improves accuracy and limit of detection but adds cost, complexity, and time. CO 2 absorption is less expensive and complex but is also less accurate than benzene synthesis. , A much simpler approach, only suitable for liquid samples, is direct counting without any sample preparation. All these techniques involve a liquid scintillation counter to detect byproducts from the radioactive decay of 14 C. The energy of the decay byproducts is converted to photons by a “cocktail” solution and further detected and amplified by the counter. ,, Although significantly more straightforward, the precision of direct counting is poor by comparison because of quenching properties related to different colors of the liquid that lead to loss of counts. Different products require their own baseline analysis to determine quenching effects.…”
Section: Established Methods For Measuring Biogenic Carbonmentioning
confidence: 99%
“…A previous study showed that increasing the counting time improved precision (0.2% absolute for 2% of biogenic content with 180 min of counting time), comparable with AMS and LSC-benzene. Direct LSC has been used to track biogenic carbon in a wide range of fuel blends, ethanol/gasoline, diesel, HVO, and FAME, ,, and better results were obtained with higher biogenic concentrations. As noted, biogenic content of FCC coprocessing outputs may be at relatively low percentages (<10 wt %) and applying this technique requires long analysis times.…”
Section: Established Methods For Measuring Biogenic Carbonmentioning
confidence: 99%
“…The second is the benzene method (LSC-B; Horvatinčić et al 2004), where 14 C determination occurs after sample conversion to benzene by forming carbide followed by hydrolyzation to acetylene and the trimerization to get benzene (Horvatinčić et al 2004;Krištof and Kožar Logar 2017). Another procedure avoids sample pretreatment altogether (LSC-C), and involves simply mixing an appropriate scintillation cocktail with the sample (Norton et al 2012;Culp et al 2014;Krištof 2015;Doll et al 2017;Krajcar Bronić et al 2017;Doll et al 2021).…”
Section: Introductionmentioning
confidence: 99%